Influence of job satisfaction on SRH and happiness among Korean disabled workers: findings from the panel survey of employment for the disabled 2016–2018 - Lee, Young Lim; Yang, Jeong Min; Kim, Jae-Hyun (Frontiers in Public Health, 2023)
Background An understanding of the economic life activities of persons with disabilities (PWD) is important. Their ability to perform tasks and an increase in their income are more likely to yield an improvement in their Self-Rated Health (SRH) and happiness. However, there is still a lack of understanding of the specific associations among PWD in South Korea. Thus, this study conducted a longitudinal analysis of the association between job satisfaction and SRH, happiness among the Korean PWD. Methods After excluding missing values, data on 1,637 participants at baseline (1st wave) were analyzed using the chi-square test, t-test, Analysis of Variance (ANOVA) and generalized estimating equation (GEE) model for data from 1st to 3rd Panel Survey of Employment for the Disabled (PSED). All analyses were conducted using the SAS statistical software package, version 9.4. Results Compared to very high job satisfaction group, low job satisfaction group was more likely to experience negative SRH [odds ratio (OR): 3.497, value of p: <0.0001] and experience low happiness (B: −0.291, value of p: <0.0001). Furthermore, in terms of the overall satisfaction with current job among the PWD, compared to the ‘very satisfied’ group, ‘very unsatisfied’ group had higher negative SRH (OR: 5.158, value of p: 0.003) and lower happiness (B: −0.327, value of p: <0.0001). Conclusion This study suggests that increasing job satisfaction of PWD possibly leads to decreased negative SRH and to increased happiness, resulting in better SRH and happiness. Furthermore, it suggests the establishment of systemic, policy-oriented measures to enhance the employment opportunities for disabled individuals in Korea and create an inclusive working environment that aligns with their respective job responsibilities.